Outcomes of HIV Positive Children and Adolescents Initiated on Antiretroviral Treatment in Nigeria (2007-2016). (August 2022) - Anukam, Onyekachi; Blanco, Natalia; Jumare, Jibreel; Lo, Julia; Babatunde, Ezra; Odafe, Solomon; Onotu, Dennis; Ene, Uzoma; Fagbamigbe, Johnson; Carpenter, Deborah; Rivadeneira, Emilia D.; Omoigberale, Austin I.; et al.
Background: This manuscript aimed to examine treatment outcomes of HIV-positive children and adolescents.Methods: We retrospectively analyzed data of a sample of patients aged 0–19 years who initiated ART (October 2007–September 2016) in participating sites in 30 states and the Federal Capital Territory in Nigeria.Results: Among 4006 patients alive at the end of the follow up period, 138 (3.4%) were LTFU. Adolescents had a significantly higher risk of being LTFU than children aged 3–5 years (HR 2.47 [95% CI 1.40-4.34]). Patients with advanced disease had a significantly higher risk of being LTFU (Stage IV HR, 3.66 [95% CI: 2.00-6.68]). On average, optimal ART refill adherence was met by 67.3% of patients.Conclusion: Our findings suggest that focusing on preventing and managing advanced disease and interventions supporting adolescents when transferring to adult care is warranted.